Midwifery Care for Postpartum Mothers With Difficulty Urinating Discomfort at the Clinic: Asuhan Kebidanan pada Ibu Nifas Dengan Ketidaknyamanan Sulit Berkemih di Klinik - Putri, Aprecia Amalia Suhadak; Machfudloh, Hanik (Indonesian Journal of Innovation Studies, 2020)
The postpartum period is a period of adaptation of the mother after giving birth, this period includes the change from the condition of the pregnant woman to the condition before pregnancy, starting after the placenta is born and ending when the uterus returns to its pre-pregnancy state. During this period, physiological changes occur during the puerperium. Based on research in 2017 it was found that 94.12% of respondents did bladder training to get the urinary system muscles active again. The purpose of this case study is to describe the discomfort of difficulty urinating in postpartum mothers, while the method used by the case study is a descriptive method. This case study was taken from December 30, 2019 to February 2, 2020. The midwifery care used in the case study was assessment and evaluation. In the implementation of the case study, no complications were found, and there was no gap between discomfort and supporting theory.